Effects of body condition score and parity on reproduction efficiency of Bonsmara cows in timed artificial insemination programmes - Webb, E.C. (Edward Cottington) (University of Pretoria, 2022)
Dissertation (MSc Agric (Animal Science: Production Physiology and Production Quality))--University of Pretoria, 2021.